IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN MENULIS TEKS PUISI RAKYAT DI SMP NEGERI 8 PADANG - Fahmesvi, Bunga; Atmazaki, Atmazaki (Universitas Negeri Padang, 2020)
ABSTRACT This study aims to illustrate the following. First, describing the implementation of character education in write text of folk poetry in SMP Negeri 8 Padang including planning, implementing, and evaluating learning. Secondly, it describes the supporting and inhibiting factors of Indonesian language learning in SMP Negeri 8 Padang, which have character education. This research method is a combination of current triangulation design. The research sample was taken 25% with a proportional random sampling technique of 32 respondents. There are five results of this study. First, a learning plan consisting of a syllabus and a lesson plan (RPP) focuses on three character values, namely religious, creative, and collaboration. Second, the implementation of learning is supported by the results of interviews and the level of achievement of respondents preliminary activities (80.31%), core activities (77.43%), and closing activities (78.04%). Third, the assessment of learning shows an overall achievement level of 78.28% with a good category. Fourth, school programs, teachers, and facilities and infrastructure are supporting factors for learning Indonesian with character. Fifth, the lack of facilities and environmental influences is a barrier to the realization of character education in learning. Kata Kunci: Implementasi Pendidikan Karakter dan Pembelajaran Menulis Teks Puisi Rakyat